„Mowa obrończa” metodologii archeologów Uniwersytetu im. Adama Mickiewicza w Poznaniu - Mamzer, Henryk (Folia Praehistorica Posnaniensia, 2020)
This text contains an interpretation of the intellectual activity of methodologists of archaeology from the Adam Mickiewicz University in Poznań. The idea they implement is – in my opinion – a way of thinking: from an object to thinking about an object, addressed both to archaeologists who are not convinced of methodology and to representatives of cultural archeology, in order to finally signal their contribution to integrated humanities. I tried to highlight the effects of this activity in such a way that its real benefits for each of the recipients mentioned were visible.